Altered Brain Regional Homogeneity Following Electro-Acupuncture Stimulation at Sanyinjiao (SP6) in Women With Premenstrual Syndrome - Pang, Yong; Liu, Huimei; Duan, Gaoxiong; Liao, Hai; Liu, Yanfei; Feng, Zhuo; Tao, Jien; Zou, Zhuocheng; Du, Guoxiang; Wan, Rongchao; Liu, Peng; Deng, Demao (Frontiers in Human Neuroscience, 2018)
Background: Premenstrual syndrome (PMS) is a menstrual cycle-related disorder which causes physical and mood changes prior to menstruation and is associated with the functional dysregulation of the brain. Acupuncture is an effective alternative therapy for treating PMS, and sanyinjiao (SP6) is one of the most common acupoints used for improving the symptoms of PMS. However, the mechanism behind acupuncture’s efficacy for relieving PMS symptoms remains unclear. The aim of this study was to identify the brain response patterns induced by acupuncture at acupoint SP6 in patients with PMS. Materials and Methods: Twenty-three females with PMS were enrolled in this study. All patients underwent resting-state fMRI data collection before and after 6 min of electroacupuncture stimulation (EAS) at SP6. A regional homogeneity (ReHo) approach was used to compare patients’ brain responses before and after EAS at SP6 using REST software. The present study was registered at http://www.chictr.org.cn, and the Clinical Trial Registration Number is ChiCTR-OPC-15005918. Results: EAS at SP6 elicited decreased ReHo value at the bilateral precuneus, right inferior frontal cortex (IFC) and left middle frontal cortex (MFC). In contrast, increased ReHo value was found at the bilateral thalamus, bilateral insula, left putamen and right primary somatosensory cortex (S1). Conclusions: Our study provides an underlying neuroimaging evidence that the aberrant neural activity of PMS patients could be regulated by acupuncture at SP6.